Herniation of the Bladder into the Rectum in a Dog - Lambrechts, N. E. (Veterinary and Comparative Orthopaedics and Traumatology, 1990)
In the dog, the pelvis is frequently injured following motor vehicle accidents (1). Injuries to the lower urinary and intestinal tracts may accompany pelvic fractures in man (2, 3, 4, 5) and the dog (1, 6, 7). This paper describes an unsual case of bladder retroflexion and herniation through a tear, into the rectum of a dog, following traumatic fracture of the pelvis. The successful management and repair is outlined and a biomechanical sequence leading to the abnormal bladder position is proposed.An unusual case of bladder retroflexion and herniation through a tear, into the rectum of a dog, following traumatic fracture of the pelvis is described. Repair was accomplished by manipulation of the bladder into its normal position through a coeliotomy incision and suturing of the rectal tear after prolapsing the rectum through the anus. The proposed biomechanical sequence leading to this injury is tearing by the inwardly rotated, fractured left hemipelvis as well as or alternatively, shearing forces along lines of excessive tension.
Keywords: Dog; Bladder herniation; Rectal laceration; Pelvic fracture